1‐(2, 6‐dibenzhydryl‐4‐fluorophenylimino)‐2‐aryliminoacenaphthylylnickel halides highly polymerizing ethylene for the polyethylenes with high branches and molecular weights. Issue 11 (3rd March 2015) - Fan, Linlin; Du, Shizhen; Guo, Cun‐Yue; Hao, Xiang; Sun, Wen‐Hua
ABSTRACT: A series of 1‐(2, 6‐dibenzhydryl‐4‐fluorophenylimino)‐ 2‐aryliminoacenaphthylene derivatives (L1–L5 ) and their halonickel complexes LNiX2 (X = Br, Ni1–Ni5 ; X = Cl, Ni6–Ni10 ) are synthesized and well characterized. The molecular structures of representative complexesNi2 andNi4 are confirmed as the distorted tetrahedron geometry around nickel atom by the single crystal X‐ray diffraction. Upon activation with methylaluminoxane, all nickel complexes show high activities up to 1.49 × 10 7 g of PE (mol of Ni) −1 h −1 toward ethylene polymerization, producing polyethylenes with high branches and molecular weights up to 1.62 × 10 6 g mol −1 as well as narrow polydispersity. © 2015 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2015, 53, 1369–1378 Abstract : The 1‐(2, 6‐dibenzhydryl‐4‐fluorophenylimino)‐2‐aryliminoacenaphthylylnickel halides, activated with methylaluminoxane, show high activities toward ethylene polymerization, producing polyethylenes with high branches and molecular weights as well as narrow polydispersity.